If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + -2) = 2(3 + 6x) Reorder the terms: 5(-2 + 4x) = 2(3 + 6x) (-2 * 5 + 4x * 5) = 2(3 + 6x) (-10 + 20x) = 2(3 + 6x) -10 + 20x = (3 * 2 + 6x * 2) -10 + 20x = (6 + 12x) Solving -10 + 20x = 6 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -10 + 20x + -12x = 6 + 12x + -12x Combine like terms: 20x + -12x = 8x -10 + 8x = 6 + 12x + -12x Combine like terms: 12x + -12x = 0 -10 + 8x = 6 + 0 -10 + 8x = 6 Add '10' to each side of the equation. -10 + 10 + 8x = 6 + 10 Combine like terms: -10 + 10 = 0 0 + 8x = 6 + 10 8x = 6 + 10 Combine like terms: 6 + 10 = 16 8x = 16 Divide each side by '8'. x = 2 Simplifying x = 2
| 15x-2x=-7x | | 42x-210=27x | | 3+10a-8=15 | | 6x-9+2x=5+8x-13 | | 2+x+y=x+5 | | 2x-2+2y=2+x+y | | 5r^2-19r-4= | | -3p+2+4p=-5 | | +65+(x-5)=180 | | x^4+15x-30= | | 7+20x=4(5x+3) | | 4y+9=3y-3 | | +65+(x-5)=60 | | 1.01*0.231= | | 6=-0.2r | | 5x+6=2x+13 | | 3x+2=3+x+3 | | 7y-14-4y+9=0 | | T=hp+b | | 3x+2=3+x-3 | | 3x+2=3+x-y | | 4x+7+5x=6x-11 | | 12=3h+4-h | | 3x-2=18x+8 | | Y-2=7(x+1) | | -1+6x=65 | | 6=0.9 | | 3b+4=30 | | -7+2x+x+10=8 | | -5x+8=-52 | | 16+5v=1+3v-1 | | 9-5+2*8= |